Chemico-pharmacological evaluation of the methanolic leaf extract of Catharanthus ovalis: GC–MS/MS, in vivo, in vitro, and in silico approaches - Saimon Shahriar; Samia Akter Shermin; Hasin Hasnat; Faisal Hossain; Aixia Han; Peiwu Geng; Safaet Alam; Abdullah Al Mamun (Frontiers in Pharmacology, 2024)
Introduction: Natural plant-based medicines have gained popularity recently as a major source of inventive, risk-free, and more potent secondary bioactive compounds with medicinal potential. Catharanthus ovalis is a perennial shrub containing various indole alkaloids cultivated extensively for local medical purposes.Methods: This research is conducted to identify the phytocompounds present in the leaves of C. ovalis and its central and peripheral analgesic, thrombolytic, and membrane-stabilizing activities through tail immersion, acetic acid-induced writhing, human blood clot lysis, and erythrocyte lysis by heat and hypotonic solution methods, respectively.Results and discussion: A total of 39 compounds were identified using GC–MS/MS techniques, including hexadecanoic acid, methyl ester (56.749%), methyl stearate (29.782%), carvacrol and its TBDMS derivative (12.586%), and 9-octadecenoic acid, methyl ester, (E)-] (9.297%) presented in high quantity. The highest tail immersion latency was observed for the 600 mg/kg extract of C. ovalis crude extract. Both 400 and 600 mg/kg doses of C. ovalis crude extract exhibited prominent peripheral analgesic activity. The maximum thrombolytic effect was observed by DCM soluble fraction extract by inhibiting 54.87% of the clot. However, the aqueous-soluble fraction of this extract manifested an excellent membrane-stabilizing effect by showing 73.98% and 87.51% hemolysis against heat- and hypotonic-induced hemolysis, respectively. Some of the compounds were identified as active agents against different receptors related to these diseases, which supported the findings of in vitro and in vivo tests.Conclusion: Further investigation needs to be conducted to specify and identify the exact mechanism of action of these compounds.